Influence Theory Fraud Hexagon Against Fraudulent Financial Reporting (Empirical study on companies included in the 27 business indexes listed on the Indonesian Stock Exchange in 2018-2022) - Amarullah Amarullah; Sri Wineh; Gita Suliska; Rd Ade Tribuana Anjaya (Nomico, 2025)
This study aims to determine the effect of Fraud Hexagon on Fraudulent financial statements. The Independent variables used in this study are Stimulus Opportunity, Rationalization, Capability, Ego, and Collusion, in this study, Financial Report Fraud is measured using the Beneish M-Score. The population used in this study are companies included in the Business Indek 27 Listed on the Indonesia Stock Exchange(IDX) during The 2018-2022 period.The sampling method, the samples obtained were 11 companies. The data in the form of financial reports. Data analysis uses logistic regression analysis with the help of cafhvare SPSS 29.The Result of this study indicate that the Stimulus, Opportunity, Rationalization, Capability and Collusion variabel do Not affect Fraudulent Financial Reporting, While the Ego Variabel affect Fraudulent Financial Reporting.